Strengthen and weakness of modeling in women entrepreneurship of small and medium scale enterprises - Puspa Liza, Ghazali; Mohamad Zulkifli, Abdul Rahim; Dede Ansyari, Guci (2017)
On this era, women entrepreneurship increase quickly at Small and Medium Enterprises (SMEs). Man and women has no difference to run a business and become entrepreneur. Small and Medium Scale Enterprises (SMEs) play significant roles in providing employment opportunities, alleviating poverty, empowering communities, provision of goods and services, contributing toward the GDP and achieving sustainable growth and development of the economy. Besides that, strengthen and the weakness of previous modeling of Women entrepreneurs such as Knowledge, Marketing, Finance, Expertise Labour (Training Labour) and Government Support on women entrepreneurship. This article discuss whether the item of previous model does enough item for the women entrepreneurs for survive in their business. The conclusion of previous models of women entrepreneurship need to add more item for women entrepreneurs to survive their businesses.